Effectiveness of Hydration Education on Fluid Consumption Patterns of Petanque Athletes in FOPI South Sulawesi - Ishak Bachtiar; Abdul Malik Asikin; Andi Muhammad Dzulkifli; Rahmadani, Suci; Ponggalang, Monalisa (Universitas Negeri Jakarta, 2025)
Optimal hydration plays a vital role in maintaining athletic performance, particularly in precision-based sports such as Petanque, which require concentration, energy stability, and high mental endurance. However, athletes’ understanding of proper hydration practices remains limited, increasing the risk of dehydration, reduced focus, and performance decline. This study aimed to analyze the effectiveness of hydration education delivered through digital and printed media in improving the knowledge and fluid consumption behaviors of Petanque athletes under the Federation of Petanque Indonesia (FOPI) South Sulawesi. The research employed a quantitative approach using a one-group pretest–posttest design involving 35 athletes selected through total sampling. The educational intervention was implemented via an educational website and an athlete hydration handbook, while data were collected using pre-test and post-test questionnaires. The findings revealed a significant improvement in athletes’ knowledge and hydration behaviors after the intervention, confirming the effectiveness of the educational program in fostering positive behavioral changes. The results emphasize the applicability of health behavior change theories in sports nutrition education and demonstrate that interactive, media-based education can effectively enhance both awareness and practice. Theoretically, this study contributes to expanding the application of hydration education in non-cardiorespiratory sports, while practically, it provides a foundation for developing structured training programs that highlight the importance of fluid balance as a key determinant of athletic performance and overall well-being.